2016
DOI: 10.1038/srep38413
|View full text |Cite
|
Sign up to set email alerts
|

Probing the role of cation-π interaction in the thermotolerance and catalytic performance of endo-polygalacturonases

Abstract: Understanding the dynamics of the key pectinase, polygalacturonase, and improving its thermotolerance and catalytic efficiency are of importance for the cost-competitive bioconversion of pectic materials. By combining structure analysis and molecular dynamics (MD) simulations, eight mutagenesis sites having the potential to form cation-π interactions were identified in the widely used fungal endo-polygalacturonase PG63. In comparison to the wild-type, three single mutants H58Y, T71Y and T304Y showed improved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The data obtained on the basis of UV spectra of P. restrictum α-L-rhamnosidase indicate a significant contribution of aromatic amino acids to both, possibly, the topology of the active center, and the thermal stabilization of the enzyme in the presence of compound (7) due to weak cation-π interactions. In recent years, studies have appeared showing the importance of cation-π interactions both for the manifestation of the catalytic properties of enzymes and for their thermal stabilization [19]. There is evidence that, in mesophiles, Phe residues play a key role in the cation-π interaction, while for thermophiles Tyr has a greater effect [20].…”
Section: Resultsmentioning
confidence: 99%
“…The data obtained on the basis of UV spectra of P. restrictum α-L-rhamnosidase indicate a significant contribution of aromatic amino acids to both, possibly, the topology of the active center, and the thermal stabilization of the enzyme in the presence of compound (7) due to weak cation-π interactions. In recent years, studies have appeared showing the importance of cation-π interactions both for the manifestation of the catalytic properties of enzymes and for their thermal stabilization [19]. There is evidence that, in mesophiles, Phe residues play a key role in the cation-π interaction, while for thermophiles Tyr has a greater effect [20].…”
Section: Resultsmentioning
confidence: 99%
“…The structure α,α,α-TNB (3) is about 8 and 5 kcal/mol less stable than β,β,β-TNB (6) at the B3LYP/def2-QZVP and M06-2X/ def2-QZVP levels, respectively. The peri-repulsion plays a key factor for higher relative energy of α,α,α-TNB (3) compared to β,β,β-TNB (6). Previously, the experimental study has reported the attractive and repulsive effects in the interactions of different functional groups in peri-disubstituted naphthalene.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Cation−π interaction is now well recognized by the chemical and biological sciences community as an important contributor of nonbonding interactions in macromolecular structures, drug–receptor interactions, protein–protein interactions, and neurobiology. It plays an important role in catalysis, , protein structure determination, and molecular recognition processes within ion channels and enzymes. In-depth knowledge on the cation−π interactions will certainly benefit environmental science and mineral surface chemistry . Cation−π interactions mainly include electrostatic, inductive, and charge transfer effects .…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme shares a parallel β-helix structure. Factors related to improved thermostability of enzymes include hydrophobic interactions, hydrogen bonds, , salt bridges, , cation−π bond interactions, aromatic ring interactions, , and disulfide bonds . There are four highly conserved disulfide bonds in PG.…”
Section: Discussionmentioning
confidence: 99%